The Link Between Obesity and Asthma: A Canadian Perspective - Louis-Philippe Boulet; Annick Des Cormiers (Canadian Respiratory Journal)
Asthma is considered to be more prevalent in obese subjects, and a possible causal link between these two entities has been suggested. In the present study, various observations on this relationship were reviewed, and an analysis of data obtained from the 2000 to 2001 Canadian Community Health Survey on the prevalence of self-reported asthma, medication use and allergy, according to body weight, was reported. Asthma medication use and self-reported asthma were more prevalent in the obese population, particularly in women. Mean body mass index was higher in the asthmatic population compared with the nonasthmatic population. Self-reported nonfood-related allergies were higher in the more obese subjects in the general population, but the prevalence of allergy was not different in obese asthmatic subjects compared with nonobese asthmatic subjects. Smoking did not seem to influence the relationship between asthma and body mass index. Further research should investigate the mechanisms by which obesity may influence the prevalence of asthma or asthma-like symptoms.